Structure of ubiquitylated-Rpn10 provides insight into its autoregulation mechanism - Tal Keren-Kaplan (Nature Portfolio, 2016)
Ubiquitin (Ub) receptors are responsible for the recognition of ubiquitylated proteins. Here the authors describe the crystal structure of the ubiquitylated form of the Ub-receptor Rpn10, which suggest that ubiquitylation of Rpn10 promotes its dissociation from the proteasome.